Desenvolvimento inicial de teca (tectona grandis) em resposta à fertilização com NPK em diferentes condições edafoclimáticas no estado do Pará - FERREIRA, Adélia Ribeiro (Universidade Federal do Pará, 2018)
The areas headed for reforestation generally have law fertility, and then they demand a balanced fertilizing to provide levels of compatible nutrients according to each specie. Therefore it is necessary the property value of reference more accurate to the fertilization recommendation of forest species. The studies published about teak fertilization under field conditional are so scare, this paper aims to evaluate the influence fertilization with N, P and K of climatic factors in the growth of the teak, in different soil conditions of Para state. The fertilization test constitutes of a factory experiment with dose of N and K applied on teak at the Vigia and Santa Maria das Barreiras cities, in experimental design in randomized blocks with three repetitions, in factorial arrangement 4 x 2 m, it is four doses of nitrogen and two of potassium, totaling eight treatments and 24 experimental plots. And other factorial experiment with doses of P and N applied in teak at the Vigia and Santa Maria de Barreiras cities, with design in randomized blocks and three repetitions in factorial arrangements 4 x 2 m, it is four doses of phosphor and two doses of nitrogen, totaling eight treatments and 24 experimental plots. The growth in H and DAP of teak submitted to doses of N and K at Vigia and Santa Maria das Barreitas cities, to 30 months of age, It was not significantly influenced by N x K factor, it is not happened the growth on these two variable owing to elevation of N x K doses applied in soil. At the soil conditions studied at Vigia city, the maximum growth in H was achieved with doses of 80 g of N and 138,5 g of P plant- 1, and the maximum growth in DAP was achieved with doses of 80g of N and 206 g of P plant-1, while the soil conditions studied at Santa Maria das Barreiras city, the maximum growth in H was achieved with doses of 40 g of N and 140,62 g of P plant-1, and the maximum growth in DAP was achieved with doses of 40 g of N and 161,25 g of P plant-1. The IPDAP showed a relationship between the precipitation seasonality with the high values of IPDAP happened on the rainy period and lower values happened on the less rainy period.